2017
DOI: 10.30971/pje.v34i1.183
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Generic Competence Development among Higher Education Students

Abstract: Present study intended to assess the generic competences of higher education students. Self-perceived level of generic competences of the students in the beginning and the end of an academic session was recorded to explore the role of higher education in imparting them the generic competences. All the students entering the University of Sargodha (Pakistan) during 2012, constituted the population of the study. Cluster sampling technique was used to carry out the panel survey. The same cohort of the students was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…The present study found that there was no significant difference between level of generic competence in male and female students. The finding of a similar study conducted by Shah et al (2017) contradicts the finding of this study. For example, they found that male and female have different level of generic competence.…”
Section: Scatterplot Of Generic Competence and Students' Gradescontrasting
confidence: 99%
See 4 more Smart Citations
“…The present study found that there was no significant difference between level of generic competence in male and female students. The finding of a similar study conducted by Shah et al (2017) contradicts the finding of this study. For example, they found that male and female have different level of generic competence.…”
Section: Scatterplot Of Generic Competence and Students' Gradescontrasting
confidence: 99%
“…Total 170 students of B.S Sports sciences and the player students studying in other departments of the university were the total sample. Generic competence scale was used as instrument, which were consisted of nineteen competencies and developed by the reflex project in western context and used by Shah et al (2017) in Pakistani context. The instrument includes nineteen (19) generic competences.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations